Zoonotic Sporotrichosis Epidemic Affects Children in Brazil - Ferreira, Cassio Porto; Almeida, Ana Cristina Oliveira de; Paes, Rodrigo de Almeida; Corte-Real, Suzana (Journal of Pediatric Infectious Diseases, 2015)
Sporotrichosis is caused by the dimorphic fungus Sporothrix schenckii and was first described by Benjamin Schenck in 1898. It is the most common subcutaneous mycosis in Latin America. The infection is usually acquired by inoculation of the fungus through the skin. Zoonotic transmission of sporotrichosis seems to be rare worldwide. However, since 1998, an increasing number of cases have been reported in humans in Rio de Janeiro, Brazil; the vast majority of these cases have been associated with contact with cats affected by the same condition. Itraconazole is the drug of choice for treatment.
Keywords: epidemic; sporotrichosis; zoonotic